Criminalization Provisions and the Part Related to the Crimes of Insult and Slander through Social Communication in the Libyan Legislation : A Comparative Study - Dganni, Khalid; AlShafy, Almahdi (Journal of Legal Sciences, 2023)
The importance of this topic is reflected in the need to know the legal provisions for the offenses of insult and slander within the scope of information technology, which have a great impact on people, and have been used to undermine human honor and dignity, especially that it is one of the new crimes, which has not been studied extensively by researchers, and many have tried Some countries develop their legislative systems by introducing punitive and procedural texts and legislation that are compatible with the phenomenon of modern technical crime And we decided to research the pillars of these crimes and to clarify their general provisions through exposure to the public and private pillars that prove criminal responsibility, and we found it appropriate to state the position of the Libyan law and some comparative laws on the crimes of slander and insult through social media platforms, and also to show the legislative awakening of the UAE law coinciding with the development of technology It is associated with some Libyan and Emirati judicial applications in this field, wherever it is possible for us to do so.